2015
DOI: 10.1097/tin.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Assessment Methodology for Nutritional Assessment

Abstract: Assessment of dietary intake is challenging, and all current methodologies come with their individual strengths and weaknesses. Innovative technologies to improve dietary assessment methods are emerging and seem promising. Conventional methods include food records (prospective) or recalls/diet history/food frequency questionnaires (retrospective). The appropriate method to use depends primarily on the main objective of the study, the level of detail required, and the resources available. Understanding, acknowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Smartphone apps have been shown to promote self-monitoring by reducing the burden of recording [ 20 ]. In addition, the availability of barcode scanning, nutrient databases, and image recording contributes to the reduced burden [ 35 , 36 ]. Studies have reported that the inclusion of features in apps that are user friendly and reduce time burden is more effective [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smartphone apps have been shown to promote self-monitoring by reducing the burden of recording [ 20 ]. In addition, the availability of barcode scanning, nutrient databases, and image recording contributes to the reduced burden [ 35 , 36 ]. Studies have reported that the inclusion of features in apps that are user friendly and reduce time burden is more effective [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NNS-FFQ can be self-administered, making it convenient and economical to collect large amounts of data in community or epidemiological studies [ 36 ] and could be designed to be machine-readable, making it more easily scored for analysis, and thus reducing researcher-associated costs [ 37 ]. The scale at which the NNS-FFQ can be used will make it useful for large population-level studies [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, as a retrospective measure, this food frequency questionnaire is also limited in that it relies on individuals' memory. However, its unannounced and self-administered features as well as the fact that it captures habitual behaviours are important strengths of this method ( Walton, 2015 ). Additionally, previous studies using these questions have shown that they can provide valid data on habitual dietary intake ( Kliemann et al, 2016 ; McGowan et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%